Research on Air Suspension Control System Based on Fuzzy Control. (May 2017) - Zepeng, Gao; Jinrui, Nan; Lian, Liu; Xiaolin, Xu
Abstract: In order to solve the suspension overshoot phenomenon existing in the static regulation process of the electric vehicle with electric controlled air suspension, firstly, the relevant factors of air spring are analyzed and the characteristics of the gasbag are simulated and verified in AMESim. Secondly, the model of the electric vehicle body is analyzed according to the law of dynamics and the fuzzy control theory is used to set up the electric vehicle body model in Simulink. In the case of unbalanced load, the effectiveness of the fuzzy controller is used to simulate the phenomenon of "overshoot" in the system.